Altura de pastejo da Brachiaria ruziziensis sobre a produção de palhada, atributos físicos, carbono e nitrogênio no solo e produtividade de soja em sistema de integração lavoura pecuária conduzido em latossolo arenoso - Ferreira, Gilberto Alves (2013)
The use of forage species in production systems such as integrated crop livestock can be key to improving fertility and increasing productivity of pastures and crops. The objective this study was to evaluate the effects height of grazing of Brachiaria ruziziensis on straw production, on the physical properties of the soil, in levels and stocks of carbon and nitrogen of the soil and in the soybean yield in crop livestock integration system. The experiment was conducted in the Experimental Farm of the Agronomic Institute of Paraná (IAPAR), located in the municipality of Xambrê-PR, in september 2010 to april 2012, during the agricultural year 2010/2011 and 2011/2012. The experimental design used was randomized in blocks, split plot in time (sampling time), with five treatments (grazing height of 10, 20, 30 and 40 cm and an area with no grazing) and three repetitions. Were determined the dry matter the mass of the aerial part of Brachiaria ruziziensis, vegetable residue dry matter and mass of total dry matter. The layers of 0-10, 10-20 and 20-30 cm were studied the density, macroporosity, microporosity, total porosity, gravimetric water, levels and stocks of total organic carbon, particulate carbon and carbon associated with minerals and the levels and stocks of mineral nitrogen and total of the soil. In culture of soy were evaluated the number of plants per meter, height of plants and grain productivity. The dry matter mass of the aerial part of Brachiaria ruziziensis and the total dry matter mass were significant (P<0,05) in the two seasons of evaluation, with higher production in the ungrazed compared to grazed area (P<0,05). The variable dry matter of plant residue was not significant (P>0,05) for the first time and significant in second season (P<0,05). The density, macroporosity, microporosity, total porosity and gravimetric soil moisture were not altered by grazing height and area not grazed at all depths evaluated (P>0,05). Density reduction occurred, increase macroporosity and total porosity in the 0-10 cm layer of soil, at the end of the experiment (P<0,05). There was a higher microporosity after brachiaria in relation to the time after the soybean crop (P <0,05). The levels and stocks of total organic carbon of the soil and its fractions, besides levels and stocks of mineral and total nitrogen of the soil were not altered by grazing heights and the area not grazed (P>0,05). However, there was an increase in levels and stocks of total organic carbon and carbon associated with minerals and a reduction of the particulate carbon of the soil in the final experiment (P<0,05). There was an increase of mineral nitrogen after harvest soybeans for all soil layers (P<0,05), however, the increase of total nitrogen and stocks of the soil occurred only in the 0-10 cm depth, in the last evaluation. The number of plants per meter, plant height and yield of soybean were not affected by the different Heights and the absence of grazing (P>0,05)